Vegetation Structure, Biomass, and Carbon Stock of Urban Forest of Bongohulawa National Wirakarya Campground in Gorontalo Regency - Gorontalo Province - Dewi Baderan; Sukirman Rahim; Endi Triyanto Manyo’e (Jurnal Ilmu Lingkungan, 2023)
An urban forest is one type of Urban Green Open Space (RTHKP) that reflects the character of nature and/or local culture with ecological, historical, and panoramic values that are unique to the level of technology application. The urban forest of the National Wirakarya Campsite is quite attractive, has a lovely view, is close to the road, and is easily accessible by the residents. This study aims to determine the structure of vegetation, biomass, and carbon values stored in the urban forest of the National Wirakarya Campsite, Bongohulawa, Gorontalo Regency, Gorontalo Province. The method used is a survey method with a quantitative descriptive research design. The sampling method used is a purposive sampling model based on land cover in the urban forests. For the measurement of the vegetation structure, the sampling of vegetation in the observation plots is carried out by using the number of sample plots that are placed regularly by calculating the Relative Density (RD), Relative Frequency (RF), and Relative Dominance (RDo), then the data obtained are tabulated to provide IVI. To measure the carbon stocks on the surface (stems), a non-destructive sampling method is used with an Allometric equation based on the plant species. The results showed, there were 13 families, 20 species, and 824 individuals. The vegetation structure in the urban forest of Bongohulawa National Wirakarya Campsite (PWN) has an IVI above 15 percent on average. The sawlog level is dominated by the Gmelina arborea (beechwood) species with an IVI of 98.36 percent, the pole level is dominated by the Swietenia mahagagoni (mahogany) with an IVI of 165.37 percent, the sapling level was dominated by Swietenia mahagoni with an IVI of 160.99 percent and the seedling level was dominated by Lantana camara (tembelekan) with an IVI of 32.25 percent. The content of biomass stored in the standing trees is 1,190.45 tons/ha, with the largest amount of biomass is at the sawlog level of 1,135.43 tons/year or 95.43 percent, the total biomass at the pole level is 45.10 tons/year or 3.79 percent and the amount of long-term biomass is 9.32 tons/year or 0.78 percent. The carbon stock stored (C-Stock) is 559.37 tons/ha and can absorb CO2 (CO2eq) of 2,052.88 tons/ha and provides converted O2 of 1,498.60 tons/ha.